PENGURUSAN UNDANGAN KEPESERTAAN KONVENSI FORUM REKTOR INDONESIA OLEH PT. WAHYU PROMO CITRA - Sari, Denisa Ratna; Maharani, Maharani; Setiawati, Rahmi (Journal of Indonesian Tourism and Policy Studies, 2018)
This final project assignment deals with the Invitation of Convention of Rector Indonesia Forum 2017, as well as the obstacles encountered and problem solving. Based on data collection methods used by the author is by way of direct observation to the field and literature study through books and online. The process of this activity is important in the success of the Indonesia Rector Forum Convention 2017, because in it there are several stages which is the standard for distributing invitations.